Thymopentin-Mediated Inhibition of Cancer Stem Cell Stemness Enhances the Cytotoxic Effect of Oxaliplatin on Colon Cancer Cells - Yu, Peng-Cheng; Liu, Di; Han, Zeng-Xiang; Liang, Fang; Hao, Cui-Yun; Lei, Yun-Tao; Guo, Chang-Run; Wang, Wen-Hui; Li, Xing-Hua; Yang, Xiao-Na; Li, Chang-Zhu; Yu, Ye; et al. (Frontiers in Pharmacology, 2022)
Abstract Thymopentin (TP5) is an immunomodulatory pentapeptide that has been widely used in malignancy patients with immunodeficiency due to radiotherapy and chemotherapy. Here, we propose that TP5 directly inhibits the stemness of colon cancer cells HCT116 and therefore enhances the cytotoxicity of oxaliplatin (OXA) in HCT116 cells. In the absence of serum, TP5 was able to induce cancer stemness reduction in cultured HCT116 cells and significantly reduced stemness-related signals, such as the expression of surface molecular markers (CD133, CD44 and CD24) and stemness-related genes (ALDH1, SOX2, Oct-4 and Nanog), and resulted in altered Wnt/β-catenin signaling. Acetylcholine receptors (AchRs) are implicated in this process. OXA is a common chemotherapeutic agent with therapeutic effects in various cancers. Although TP5 had no direct effect on the proliferation of HCT116, this pentapeptide significantly increased the sensitivity of HCT116 to OXA, where the effect of TP5 on the stemness of colon cancer cells through stimulation of AchRs may contribute to this process. Our results provide a promising strategy for increasing the sensitivity of colon cancer cells to chemotherapeutic agents by incorporating immunomodulatory peptides.